A new magnesium sheet alloy and its multi-stage homogenization for simultaneously improved ductility and strength at room temperature. (October 2019) - Shi, Renhai; Miao, Jiashi; Luo, Alan A.
Abstract: A new Mg-2Zn-0.3Ca-0.2Ce-0.1Mn 1 (ZXEM2000) alloy and a multi-stage homogenization process have been designed and developed based on CALculation of Phase Diagram (CALPHAD) modeling results and experimental validation. The new sheet alloy offers an excellent combination of ductility (about 29% elongation) and yield strength (157 MPa), promising room-temperature forming applications. Microstructure characterization reveals that the exceptional properties of this alloy are mainly attributed to the weak basal texture, fine average grain size and high density of nano-scale Mn and Mg6 Zn3 Ca2 precipitates achieved through multi-stage heat treatment and thermomechanical processing. Graphical abstract: Unlabelled Image